THU0540 Efficacy and safety of adalimumab in behÇet's disease related uveitis: a multicenter retrospective observational study. (15th June 2017) - Fabiani, C; Vitale, A; Emmi, G; Vannozzi, L; Lopalco, G; Guerriero, S; Orlando, I; Franceschini, R; Bacherini, D; Cimino, L; Soriano, A; Frediani, B; et al.
Abstract : Background: Current information on the use of adalimumab (ADA) in the treatment of ocular Behçet's disease (BD) is still based mainly on small series or case reports; nonetheless preliminary evidence is promising. Objectives: The study aim was to evaluate the efficacy of ADA in a large series of BD-related uveitis. Methods: We performed a multicenter retrospective observational study including 40 selected patients (66 eyes) receiving ADA. Clinical data were retrospectively analyzed at baseline, at 3 and 12 months of treatment. Primary end-point was: reduction of ocular inflammatory flares. Secondary end-points were: improvement of Best Corrected Visual Acuity (BCVA), reduction of macular thickness measured by optical coherence tomography (OCT), reduction in the occurrence of vasculitis assessed by fluorescein angiography (FA), evaluation of statistically significant differences between patients treated with ADA monotherapy and those undergoing ADA plus DMARDs and in patients firstly treated with ADA compared to patients previously administered with other biologics; ADA steroid sparing effect was also evaluated. Results: During the first 12 months of ADA therapy the number of flares significantly decreased from 200 flares/100 patients/year to 8.5 flares/100 patients/year ( p <0.0001). Similarly BCVA improved if compared to baseline (7.4±2.9 versus 8.5±2.1, p =0.03). OCT findings significantly improved showing a mean reduction of central macular thickness (CMT) of 27.27±42.8 microns at the end of follow up ( p <0.006). FA identified retinal vasculitis in 22 cases at baseline (55%), 8 (20%) cases after 3 months and in only one (2.5%) case at 12-month follow-up. FA improvement was highly significant at 3 and 12-month follow-up if compared to baseline ( p <0.0001 and p =0.006, respectively). Conclusions: ADA is highly effective and safe for the treatment of BD-related uveitis, providing a long-term control of ocular inflammation. Disclosure of Interest: None declared